Aplikasi Registrasi Administrasi Lembaga Swadaya Pada Kantor Desa Talang Nangka Berbasis Web - Yanto, Mesdi (Universitas PGRI Yogyakarta, 2023)
Office of the Head of Talang Nangka Village, Lembak District, Muara Enim Regency. The method of recording, registering and submitting information from the Talang Nangka Village Non-Governmental Organization still uses a simple method which causes frequent errors and the risk of data loss may occur. The purpose of this study was to build an application using a website to make it easier for Talang Nangka Village to process the administrative processing of this village self-help organization, because it is well computerized and easy to use. The research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and literature study. The type of data consists of qualitative data and data sources consist of primary and secondary data. The device development method uses a prototype. The system design tools used are use case diagrams, activity diagrams, and class diagrams. This application was built using a website with the PHP programming language and Mysql database, and to print the report using a pdf component